Bin weather data for different climates of Turkey - Pusat, Saban; Ekmekci, Ismail (INDERSCIENCE ENTERPRISES LTD, 2017)
In this study, bin weather data and bin method for Turkey which is a well-known and simple method to estimate heating and cooling loads were investigated. The bin weather data for dry-bulb temperature from -50 degrees C to +50 degrees C with 3 degrees C increments were generated in six daily 4-h shifts. Typical meteorological year datasets were used to generate bin weather data for the selected eight cities (Istanbul, Ankara, Trabzon, Van, Diyarbakir, Adana, Sivas and Denizli) representing the distinct climatic zones of Turkey. Using typical meteorological year data in bin data generation is the original part of this study. Yearly total.bin values for the selected cities were tabulated. Results of this study are important due to the data used, fill an important gap for Turkey about bin data and can simply be used in prediction of heating and cooling energy consumptions of buildings. Additionally, this study contributes well to the world literature on bin data.
Keywords: bin data; typical meteorological year; TMY; energy analysis; heating load; cooling load; Turkey; climate; BUILDING ENERGY EFFICIENCY; GREEK CITIES; SYSTEMS; PROVINCES; ANATOLIA; DESIGN; CHINA; MODEL; Environmental Sciences & Ecology